1994
DOI: 10.1063/1.112654
|View full text |Cite
|
Sign up to set email alerts
|

Limitation due to three-photon absorption on the useful spectral range for nonlinear optics in AlGaAs below half band gap

Abstract: We report measurements of the spectral dispersion and the magnitude of three-photon absorption in Ale,sGa,,s,As for photon energies between one half and one third the band gap and show that a two-parabolic-band model is valid in this material. These results indicate that there is a limited spectral range below half the band gap in AlGaAs (and presumably all semiconductors) in which the bound electronic optical nonlinearity can be used without significant multiphoton absorption.One of the hardest aspects of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 12 publications
2
41
1
Order By: Relevance
“…In particular, the 3PA spectra and n 2 wavelength dispersions are probed in detail with both femtosecond Z-scan and timeresolved pump-probe techniques. We have found that the 3PA spectra of wide-gap semiconductors fit well to a model developed by Brandi and de Araujo [19], contradicting the results for narrow-band-gap semiconductors [14]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…In particular, the 3PA spectra and n 2 wavelength dispersions are probed in detail with both femtosecond Z-scan and timeresolved pump-probe techniques. We have found that the 3PA spectra of wide-gap semiconductors fit well to a model developed by Brandi and de Araujo [19], contradicting the results for narrow-band-gap semiconductors [14]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 97%
“…A 3PA coefficient measured by Catalano et al is also added for comparison [17]. It is interesting to note that for AlGaAs semiconductor, the Wherrett's theory is experimentally verified to be more accurate [14]. Fig.…”
Section: Three-photon Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have chosen to expand rðxÞ instead of tðxÞ because expanding rðxÞ gives us a closer resemblance to the Lorentzian lineshape under the same approximation ðd/ðxÞ ( 1Þ. In the absence of nonlinearity (n 2 ¼ 0), (11) and (13) give a simple Lorentzian model for the transmission and reflection of the structure [8]. In Fig.…”
Section: Light Propagation -Single Cellmentioning
confidence: 99%